2021
DOI: 10.1371/journal.pone.0245314
|View full text |Cite
|
Sign up to set email alerts
|

Short-lived detection of an introduced vertebrate eDNA signal in a nearshore rocky reef environment

Abstract: Environmental DNA (eDNA) is increasingly used to measure biodiversity of marine ecosystems, yet key aspects of the temporal dynamics of eDNA remain unknown. Of particular interest is in situ persistence of eDNA signals in dynamic marine environments, as eDNA degradation rates have predominantly been quantified through mesocosm studies. To determine in situ eDNA residence times, we introduced an eDNA signal from a non-native fish into a protected bay of a Southern California rocky reef ecosystem, and then measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 54 publications
4
47
2
Order By: Relevance
“…If the signal from eDNA is contemporary, such changes would be reflected in eDNA sampled on an hourly basis. With a few exceptions (e.g., Ely et al, 2021;Kelly et al, 2018;Sengupta et al, 2019), the influence of sampling eDNA at different times of day has been mostly neglected in aquatic eDNA studies, and broad inferences are often made without attention to sampling time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the signal from eDNA is contemporary, such changes would be reflected in eDNA sampled on an hourly basis. With a few exceptions (e.g., Ely et al, 2021;Kelly et al, 2018;Sengupta et al, 2019), the influence of sampling eDNA at different times of day has been mostly neglected in aquatic eDNA studies, and broad inferences are often made without attention to sampling time.…”
Section: Introductionmentioning
confidence: 99%
“…If the signal from eDNA is contemporary, such changes would be reflected in eDNA sampled on an hourly basis. With a few exceptions (e.g., Ely et al, 2021; Kelly et al, 2018; Sengupta et al, 2019), the influence of sampling eDNA at different times of day has been mostly neglected in aquatic eDNA studies, and broad inferences are often made without attention to sampling time. As eDNA detections rely on stochastic observation processes, an ongoing challenge is to distinguish the signals arising from stochasticity (PCR, sequencing variation, and heterogeneous distribution of eDNA in the water) with those representing actual biological variation (e.g., diel species behavior).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of eDNA signatures is relatively rapid in marine environments [8][9][10], with laboratory experiments showing degradation rates on the order of days [11][12][13]. However, in field conditions, detection of a specific eDNA point source can degrade beyond detection limits in only a few hours [14,15]. This evidence for rapid eDNA turnover rates suggests that eDNA signatures at a given location could be highly dynamic over time, particularly for species that are transitory.…”
Section: Introductionmentioning
confidence: 99%
“…Monuki et al (2021) found day to day variation in marine fish eDNA composition from the same site in consistency with known fish behavior. Ely et al (2021) shows that eDNA composition changed significant across time of day and that eDNA can display considerable heterogeneity, on an hourly basis. Jensen et al (2022) sampled eDNA at a coastal site every hour for 32 consecutive hours and found differences in species composition between samples taken only one hour apart, although the most significant difference was between samples collected at midday and those collected at midnight.…”
Section: Discussionmentioning
confidence: 98%